Cellular Growth in Aerial Roots Differs From That in Typical Substrate Roots - Eskov, Alen K.; Viktorova, Violetta A.; Abakumov, Evgeny; Zotz, Gerhard (Frontiers in Plant Science, 2022)
Background and Aims In the roots of most vascular plants, the growth zone is small, the meristem and the elongation zone are sharply separated, and only meristematic cells divide. This statement is based almost entirely on studies with soil-rooted plants. Whether aerial roots of structurally dependent (= epiphytic / hemiepiphytic) species differ is virtually unexplored. Methods Growth of aerial roots in 20 structurally dependent plant species from eight families was studied ex-situ. In 12 species, we studied the anatomical structure and distribution of cortex cell lengths and rhizoderm in the growth zone. Key Results All studied aerial roots had an open apical meristem, and mitoses were not restricted to the meristem. In contrast to belowground roots, relative growth rate did not strongly increase upon transition to the elongation zone, while elongating growth was often prolonged. Still, the relative growth rate was lower than in belowground roots in soil and in different species it did not change considerably compared to each other. Conclusions A distinct elongation zone with rapid cell growth was missing in the studied aerial roots. Rather, there was a growth zone in which division, growth and differentiation co-occurred. We observed a generally low relative growth rate in aerial roots and a surprisingly similar initial growth pattern in spite of the diversity in taxonomy and ecology, which resembled initial cellular growth in leaves, stems and fleshy dicotyledonous fruit.